Study on the Relationship Between the Depth，Hardness and Shear Strength of the Inductively Effective Hardening Case on the Surface of 40Cr Steel Pin for Chain - Yibing Chen (Jixie chuandong)
In view of 40Cr material chain pin，in order to meet the requirements of its comprehensive performance requirements of shear strength and wear resistance under different working conditions，it is necessary to master the relationship between different surface induction hardening requirements and shear strength of chain pin. Through set different requirements for surface heat treatment of pins，the shear strength test is carried out，and the surface induction effective depth of hardening case，the relationship between shear strength and surface hardness is comprehensively analyzed. And through the establishment of this relationship on the basis of the size of the parts suitable parameters，achieve good matching equipment use function requirements. The practice shows that good results can be obtained in the design and application of pins of bucket elevator chain in cement industry by mastering the relationship between effective hardening layer depth，surface hardness and shear strength.